Research Progress on Classical Prescriptions in Treating Mammary Glands Hyperplasia - Jiang, Xin; Wang, Zhenliang (Chinese medicine and natural products, 2022)
According to Zhongjing Zhang's academic thought, gynecological diseases mostly result from deficiency, accumulated cold, and qi stagnation, so the treatment of gynecological miscellaneous diseases should take qi and blood as the general principle, and focus on the liver. The pathogenesis of mammary glands hyperplasia (MGH) is liver and kidney deficiency, disharmony of the thoroughfare vessel and the conception vessel, the causes of which are emotional imbalance, liver qi depression, and failure of transportation due to spleen deficiency. The superficial causes include qi stagnation, phlegm coagulation, and blood stasis, which are mainly related to the liver, spleen, kidney, the thoroughfare vessel, and the conception vessel. In clinical treatment of MGH, Xiaochaihu Decoction or Sini Powder can be used for qi stagnation syndrome, Xiao Xianxiong Decoction for phlegm coagulation syndrome, Guizhi Fuling Pill or Dahuang Zhechong Pill for spleen deficiency syndrome, and Wenjing Decoction for the deficiency-cold syndrome.
Keywords: mammary glands hyperplasia; Sini Powder; Xiao Xianxiong Decoction; Guizhi Fuling Pill; Dahuang Zhechong Pill; Xiao Jianzhong Decoction; Wenjing Decoction; Yanghe Decoction